2021
DOI: 10.1136/bmjdrc-2021-002447
|View full text |Cite
|
Sign up to set email alerts
|

Beta-cell failure rather than insulin resistance is the major cause of abnormal glucose tolerance in Africans: insight from the Africans in America study

Abstract: IntroductionUncertainties exist on whether the main determinant of abnormal glucose tolerance (Abnl-GT) in Africans is β-cell failure or insulin resistance (IR). Therefore, we determined the prevalence, phenotype and characteristics of Abnl-GT due to β-cell failure versus IR in 486 African-born blacks (male: 64%, age: 38±10 years (mean±SD)) living in America.Research design and methodsOral glucose tolerance test were performed. Abnl-GT is a term which includes both diabetes and prediabetes and was defined as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
(47 reference statements)
1
13
0
Order By: Relevance
“…While the pathogenesis of diabetes in SSA is poorly understood, some studies have shown that the phenotype of diabetes in Africa is distinct, with most Africans developing diabetes at a younger age (<50 years), at a relatively leaner body size (normal BMI), and with betacell secretory dysfunction [69]. Ishimwe and colleagues have shown that beta-cell failure rather than insulin resistance may be the underlying cause of abnormal glucose tolerance among African immigrants [70]. Since obesity and smoking are associated with beta-cell dysfunction, [71] interventions targeting these risk factors, which are more prevalent in HICs, may prevent CMD among African immigrants [61].…”
Section: Discussionmentioning
confidence: 99%
“…While the pathogenesis of diabetes in SSA is poorly understood, some studies have shown that the phenotype of diabetes in Africa is distinct, with most Africans developing diabetes at a younger age (<50 years), at a relatively leaner body size (normal BMI), and with betacell secretory dysfunction [69]. Ishimwe and colleagues have shown that beta-cell failure rather than insulin resistance may be the underlying cause of abnormal glucose tolerance among African immigrants [70]. Since obesity and smoking are associated with beta-cell dysfunction, [71] interventions targeting these risk factors, which are more prevalent in HICs, may prevent CMD among African immigrants [61].…”
Section: Discussionmentioning
confidence: 99%
“…The Africans in America cohort was established to assess both the well-being and cardiometabolic health of African-born Blacks living in the United States [ 23 , 25 , 26 , 27 , 28 ]. The recruitment methods included announcements on the NIH website, flyers, presentations at community events (in-person and virtual) and previous participant referrals.…”
Section: Methodsmentioning
confidence: 99%
“…While the glucose to insulin ratio provides potentially useful indication of insulin sensitivity in the absence of diabetes, this measure loses utility with elevated fasting glucose ( 5 ). Clinically relevant models validated against the gold standard euglycemic clamp include those assessing basal glucose and insulin homeostasis [e.g., the homeostasis model of insulin resistance (HOMA-IR) and quantitative insulin sensitivity check index (QUICKI)], and those incorporating the postprandial response to a glucose challenge [e.g., Matsuda insulin sensitivity index (ISI Matsuda ), beta-cell disposition index], probing a glucose challenge response provides opportunities to assess pancreatic function and peripheral glucose disposal ( 6 , 7 ). However, mixed macronutrient tolerance tests (MMTTs) are gaining popularity as they allow for a broader probe of the nutritional phenotype, including evaluations of metabolic flexibility (i.e., fuel switching), insulin sensitivity, and lipid tolerance ( 8 14 ).…”
Section: Introductionmentioning
confidence: 99%